Analysis of factors affecting nurses' readiness to handle emergency cases - Ornai, João Cristovão Neto Mok; Prasetyo , Joko; Astutik , Reni Yuli; Borges, Francisco; Ximenes , Claudino; Costa , Horacio Sarmento Da (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Emergency situations require nurses to be well prepared to provide rapid and effective life-saving interventions. Purpose: To analyze factors influencing nurses’ readiness in managing emergency cases at Hospital Regional Eduardo Ximenes (HoREX), Baucau, Timor Leste. Method: A quantitative descriptive-analytic study with a cross-sectional design was conducted involving 84 nurses selected through total sampling. Data were collected using structured questionnaires and analyzed using univariate, bivariate (Spearman rank), and multivariate (multiple linear regression) analyses. Result: The results showed that knowledge, attitude, training, experience, and availability of Basic Life Support (BLS) equipment were significantly associated with nurses' readiness (p < 0.05). Multivariate analysis revealed that knowledge was the most dominant factor influencing nurses' readiness, followed by attitude, availability of BLS equipment, training, and experience. These variables collectively explained 85.1% of the variance in nurses' readiness. Conclusion: The study concludes that improving nurses' knowledge through continuous education and regular emergency training is essential to enhance readiness in handling emergency cases. Strengthening institutional support for training programs and ensuring adequate emergency equipment are strongly recommended to improve the quality of emergency nursing care.